Agresivitas Kelompok Tekkadan dalam Serial Anime Kidou Senshi Gundamu: Tekketsu no Orufanzu - Rendy Oktafian; Idah Hamidah; Yudi Suryadi (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2025)
This study aims to describe the aggressiveness behavior carried out by the Tekkadan group in the anime series Kidou Senshi Gundamu: Tekketsu no Orufenzu. The theory used in this research is Leonardo Berkowitz's theory of aggressiveness. The method of data collection in this research uses the method of simak catat, and this research is a qualitative research that uses analysis and descriptive process in its research. The data in this study are in the form of words, phrases, and images of behavior. The data source in this research is the anime Kidou Senshi Gundamu: Tekketsu no Orufenzu. The results of this study indicate that there are 9 data on aggressiveness behavior, 4 physical aggressiveness behaviors, 2 verbal aggressiveness behaviors, 2 threatening attitudes and behaviors, and 1 explosive emotional reaction. Based on the results of data analysis, aggressiveness behavior that appears a lot in the anime Kidou Senshi Gundamu: Tekketsu no Orufenzu is physical aggressiveness, because the anime tells about war